Corporate Social Responsibility and Islamic Microfinance Integration for Productive Waqf in Indonesia: A Conceptual Study - Hadi, Nizar Hosfaikoni; Herianingrum, Sri; Prasetyo, Ari; Shofawati, Atina; Ghamri, Mohammad (UIN Sunan Kudus, 2025)
This research attempt proposes an integration model business process modeling notation for CSR related to waqf and Islamic microfinance from a review of existing research in Indonesia. Literature about problem access to financing from CSR and institutions finance micro-Islam through waqf studied in a way critical and usable to propose an alternative model. The business process model and notation describe the proposed waqf model papers. This model has developed from CSR as a source of financing for asset-waqf productive literature. This model is expected to provide service finance through CSR and engaging participatory contracts between companies and institutions in finance micro-Islam. Besides that, by the proposed model, there is no conditional collateral, tribe interest, or terms as strict as usual enforced by the institution to finance existing conventional. Findings from the paper This will provide alternative sources of financing for waqf that are productive for starting or empowering asset waqf with funds from CSR and institutions that finance micro-Islam. This study also has implications for government and manufacturer policies. The involvement of companies and institutions that finance micro-proposed Islam in this model, it helps the government reduce expenditures for empowerment asset waqf production.